The effect of situational leadership, organizational culture and achievement motivation on the work professionalism of kindergarten teacher - Erna Kusumawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research uses a quantitative approach which aims to determine whether situational leadership, organizational culture, and achievement motivation have a simultaneous and partial effect on the professionalism of kindergarten teachers in East Jakarta. This study uses a quantitative descriptive method. The total sample in this study was a total of 120 respondents. The respondents in this study were kindergarten teachers who were in East Jakarta in the 2017 period. The sample determination used the proportionate stratified random sampling technique and then to collect data through questionnaires, interviews, and documentation. The test results prove that 1) simultaneously has an effect on the professionalism of kindergarten teachers in East Jakarta. So that the test process in the f (simultaneous) test proves the influence of situational leadership, organizational culture, and achievement motivation on the professionalism of kindergarten teachers in East Jakarta. 2) partially have an influence on the professionalism of kindergarten teachers in East Jakarta. So that the test process in the t-test (partial) proves the influence of situational leadership, organizational culture, and achievement motivation on the professionalism of kindergarten teachers in East Jakarta